2013
DOI: 10.3945/jn.113.174508
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Naringenin Prevents Intestinal Barrier Defects and Inflammation in Colitic Mice

Abstract: Intestinal barrier defects are involved in the pathogenesis of inflammatory bowel disease. The present study investigated the ameliorative effects of naringenin, a citrus polyphenol, on intestinal tight junction (TJ) barrier defects and inflammation in a murine model of colitis. In Expt. 1, using a 2 × 2 fractional design, the mice were administered water or 2% dextran sulfate sodium (DSS) in combination with feeding control or naringenin-containing diets for 9 d (severe disease stage). DSS administration caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 39 publications
6
108
0
Order By: Relevance
“…Immunohistochemical detection of claudin-3 expression in the colon of DSS-colitis mice cytokines, such as IL-6 and IL-17A. As a result, the DSS-induced colitis was mitigated (Azuma et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemical detection of claudin-3 expression in the colon of DSS-colitis mice cytokines, such as IL-6 and IL-17A. As a result, the DSS-induced colitis was mitigated (Azuma et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, lowered protein levels of ZO-1 and claudin-3 have been noted, leading to an increase in intestinal epithelium permeability. Meanwhile, because the gastrointestinal epithelium is continuously exposed to food components in the lumen, TJ regulation may be modified by these components (Azuma et al, 2013). Therefore, in the present study, we investigated the effects of isomaltodextrin (IMD) as one such component on TJs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, naringenin has been shown to protect against impairment of the intestinal barrier and inflammation in a dextran sulfate sodium-induced model of colitis. 25) These reports showed that food-or herb-derived components such as a naringenin could prevent intestinal inflammation (e.g., IBD) through enhancement of intestinal barrier function. Our results showed the enhancing effect of T. caulis on intestinal barrier function, and that T. caulis could contribute to attenuate food allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of TER data presented in this paper clearly demonstrates that EGCG increases epithelial electrical resistance and TJ protein expression levels after 18-24 hours of incubation with Caco-2 cell monolayers. These data suggest an additional mechanism underlying EGCG-mediated protection against colitis (Azuma, Shigeshiro et al 2013). Future studies on the anti-inflammatory effects of EGCG should evaluate its impact on the regulation, expression, and function of barrier related components in clinical subjects with IBD.…”
Section: Chapter 7 Conclusion: Egcg Is An Effective Anti-inflammatorymentioning
confidence: 86%